Simple Spectrophotometric Methods for the Determination of Sulfamethaxazole in Pharmaceuticals Using Folinciocalteau and Orcinol as Reagents - G. Vijaya Raja; C. Bala Sekaran; D. Winnie Teja; B. Madhuri; B. Jayasree (E-Journal of Chemistry)
Two simple, sensitive and reproducible spectrophotometric methods (Method A and Method B) were developed for the determination of sulfamethaxazole in bulk and in dosage forms. Method A is based reduction of phosphomolybdic acid present in Folin Ciocalteau reagent by the drug sulfamethaxazole in the presence of sodium carbonate to form a blue colored chromogen having maximum absorption at 760 nm. Method B is based on the diazotization of the drug by sodium nitrite in acidic medium at 5 °C followed by coupling with orcinol to form yellow colored species (λmax 390 nm). Beer’s law is obeyed in the range of 5-25 μg/mL for method A and 2-10 μg/mL for method B. Results of analysis were validated statistically and by recovery studies. These methods are successfully employed for the determination of sulfamethaxazole in various pharmaceutical preparations and biological fluids.